A novel contact prediction‐based routing scheme for DTNs. Issue 1 (10th October 2014) - Zhang, Lichen; Wang, Xiaoming; Lu, Junling; Ren, Meirui; Duan, Zhuojun; Cai, Zhipeng
Abstract: Delay/disruption tolerant networks (DTNs) make opportunistic communications by utilising the mobility of nodes. The characteristics of high mobility of nodes and high dynamicity of network topology result in an absence of instantaneous end‐to‐end path from any source to a destination and thus make routing a challenge in DTNs. To deal with this issue, researchers have investigated a variety of routing schemes for DTNs based on the prediction of future contacts, in which node mobility is explored and used. However, the previous works did not consider the instant contact information such as the last contact duration time and the instant separation time since the last contact whilst making routing decisions, leading to less prediction accuracy of future contacts and thus worse routing performance. In this paper, a novel contact prediction‐based routing scheme is proposed for DTNs to increase delivery ratio by considering the instant contact information. Specifically, to predict the contact probability of two nodes accurately, the statistical contact information, the instant contact information and the contact transitivity are comprehensively considered. The simulation evaluations show that the proposed contact prediction‐based routing substantially improves delivery ratio and reduces delivery latency and delivery overhead compared with traditional DTN routing schemes. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The encounters and separations of two mobile nodes in delay/disruption tolerant networks are modelled by an alternating renewal process model. Based on the model, a novel contact prediction‐based routing scheme is proposed, in which the prediction of future contacts of two nodes can be computed with the consideration of the instant contact information such as the previous encounter time and separation time. The extensive simulations validate the efficiency of the proposed routing scheme.